Chemical and Physical Effects of the Carrier Gas on the Atmospheric Pressure PECVD of Fluorinated Precursors. Issue 10 (7th April 2015) - Hubert, Julie; Vandencasteele, Nicolas; Mertens, Jérémy; Viville, Pascal; Dufour, Thierry; Barroo, Cédric; Visart de Bocarmé, Thierry; Lazzaroni, Roberto; Reniers, François
Abstract : The atmospheric pressure PECVD deposition and texturization of hydrophobic coatings using liquid fluorinated C6 F12 and C6 F14 precursors are investigated. The effect of the carrier gas (argon and helium) is discussed in terms of the behavior of the gas phase and of the characteristics of the deposited film. Mass spectrometry measurements indicate that the fragmentation is higher with argon while helium reacts very easily with oxygen impurities leading to the formation of Cx Fy Oz compounds. These observations are consistent with the chemical composition of the films determined by XPS and the variation in the deposition rate. Moreover, the streamers present in the argon discharge affect the morphology of the surface by increasing the roughness, which leads to the increase in the hydrophobicity of the coatings. Abstract : The effect of the carrier gas on the chemical and physical properties of fluorinated coatings synthesized from PECVD of liquid precursors (C6 F12 and C6 F14 ) is investigated. Significant differences in the fragmentation of the precursor, the deposition rates, and the chemistry, morphology, and wettability of the coatings are observed between the filamentary argon and homogeneous helium discharges.